2012
DOI: 10.1063/1.3690167
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Marangoni waves in a two-layer film in the presence of gravity

Abstract: Longwave Marangoni convection in two-layer films under the action of gravity is considered. The analysis is carried out in the lubrication approximation. A linear stability analysis reveals the existence of monotonic and oscillatory instability modes, depending on the way of heating and the value of the Biot number. Numerical simulations are performed in the case of an oscillatory instability, which takes place by heating from above. Periodic boundary conditions are applied on the boundaries of the computation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…For the liquid system described above, an oscillatory instability takes place by heating from above, i.e., for M ⊥ < 0. 19 In order to compare the predictions of the linear theory with the results of nonlinear simulations that are presented in Sec. IV, the following circumstance has to be taken into account.…”
Section: Linear Stability Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…For the liquid system described above, an oscillatory instability takes place by heating from above, i.e., for M ⊥ < 0. 19 In order to compare the predictions of the linear theory with the results of nonlinear simulations that are presented in Sec. IV, the following circumstance has to be taken into account.…”
Section: Linear Stability Theorymentioning
confidence: 99%
“…The choice of the horizontal scale L * is arbitrary, because of the scaling properties of the problem. 19 We choose…”
Section: B Longwave Evolution Equationsmentioning
confidence: 99%
“…The linear stability analysis revealed the existence of stationary and oscillatory unstable modes in this bilayer system. However, the complex coupling modes in the two-laye r flow system could not be studied by the long-wave theory [16][17][18]. Aside from that, to our knowledge, in previous works, oscillatory modes in multi-layer flow systems are all coupled with Rayleigh effects.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Nepomnyashch y and Simanovskii [18] reported nonlinear Marango ni waves in a heated two-layer film in the presence of gravity by a lubrication approximat ion. Both linear stability analysis and three dimensional nonlinear evolution study were carried out.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the dynamics of a thin two-layer system was studied in [12]. It was shown that finite-amplitude alternating rolls are stable on a square lattice.…”
Section: Introductionmentioning
confidence: 99%